THE USE OF DICTOGLOSS TECHNIQUE TO IMPROVE STUDENTS’ NARRATIVE WRITING ABILITY - Indah Mutiara Sari (ELLTER Journal, 2023)
The purpose of this study is to examine objectively whether or not there is a significant difference between the eighth-grade students' narrative writing ability before and after treatment using the Dictogloss Technique at SMPN 1 Klapanunggal, Bogor West Java in the academic year 2022/2023. The research method was quantitative. The pre-experimental of one group pretest-posttest design was used in this study. The participants in this study were the eighth- graders of SMPN 1 Klapanunggal Bogor, West Java. The sample for this study was made up of 40 students utilizing purposive sampling taken from random group. The result revealed that the degree of freedom 39 at a significant level of 0.05 is 1.68 based on the t-table. The conclusion is t-value 17.03 > t- table 1.68, and the alternative hypothesis (Hi) is accepted and the null hypothesis (Ho) is rejected. Thus, it can be inferred that there is a significant difference between the students' narrative writing ability before and after treatment using the Dictogloss Technique of the eighth-grade students at SMPN 1 Klapanunggal, Bogor West Java in the academic year 2022/2023.